Male Electorate and Electoral Mandates: Regression Analysis in Sarawak State Elections (2006–2021) - Mohammad Razi, Sitam; Tarmiji, Masron; Azizul, Ahmad; Asykal Syakinah, Mohd Ali; Ryoji, Soda; Yoshinari, Kimura (Geo Publishing, Toronto Canada, 2026)
This study examines the role of the male electorate in determining electoral outcomes in Sarawak’s state elections from 2006 through 2021. In doing so, it addresses a gap in the literature: previous work has highlighted gender‐specific turnout effects (e.g., strong associations between female turnout and victory margins), but the specific influence of the male electorate has not been separately quantified. Using official constituency‐level data from four election cycles, we employ Pearson correlation and simple linear regression to model the relationship between the number of registered male voters and the winning candidate’s vote total. In the 2006–2016 period, the male electorate size strongly predicted the winner’s votes (adjusted R² ≈ 0.73–0.86 each cycle), with a near‐one‐to‐one slope indicating that, on average, every additional vote for the winner corresponded to roughly one additional registered male voter. These findings suggest a tightly coupled mobilization of male voters alongside victorious campaigns. By contrast, in the 2021 election this relationship weakened dramatically (adjusted R² ≈ 0.33), implying that new factors disrupted the prior pattern. The collapse of the male‐vote association coincides with Malaysia’s recent enfranchisement of 18–20 year olds and changing campaign dynamics, consistent with studies showing that youth turnout did not simply replace older patterns. The results imply that while male voter mobilization was a reliable strategic focus in 2006–2016, electoral success in Sarawak’s new landscape requires engaging a broader, more diverse electorate. These findings underscore the importance of reconsidering traditional demographic assumptions under evolving political conditions.